2014
DOI: 10.1186/1465-9921-15-67
|View full text |Cite
|
Sign up to set email alerts
|

Controlled and uncontrolled asthma display distinct alveolar tissue matrix compositions

Abstract: ObjectiveWhether distal inflammation in asthmatics also leads to structural changes in the alveolar parenchyma remains poorly examined, especially in patients with uncontrolled asthma. We hypothesized that patients who do not respond to conventional inhaled corticosteroid therapy have a distinct tissue composition, not only in central, but also in distal lung.MethodsBronchial and transbronchial biopsies from healthy controls, patients with controlled atopic and patients with uncontrolled atopic asthma were pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(79 citation statements)
references
References 43 publications
3
73
2
1
Order By: Relevance
“…Importantly, in our previous study where we investigated the effect of ICS (budesonide) on ECM production in bronchial fibroblasts from patients with asthma we could show that budesonide had almost none effect on ECM synthesis (51). We could also demonstrate that lung tissue composition differs between patients with controlled and uncontrolled asthma on equivalent doses of ICS, which support the impression that patients who have remaining symptoms despite conventional ICS therapy have a pronounced ECM remodelling in both central and distal airways (52). In another study with the glucocorticoidsteroid dexamethasone, ECM was decreased in fibroblasts from healthy control subjects but not from patients with asthma that was related to increased expression of activator protein-1 (AP-1) transcription factor in fibroblasts from patients with asthma.…”
Section: Proteoglycan Syntheses Are Closely Regulated By Different Masupporting
confidence: 60%
“…Importantly, in our previous study where we investigated the effect of ICS (budesonide) on ECM production in bronchial fibroblasts from patients with asthma we could show that budesonide had almost none effect on ECM synthesis (51). We could also demonstrate that lung tissue composition differs between patients with controlled and uncontrolled asthma on equivalent doses of ICS, which support the impression that patients who have remaining symptoms despite conventional ICS therapy have a pronounced ECM remodelling in both central and distal airways (52). In another study with the glucocorticoidsteroid dexamethasone, ECM was decreased in fibroblasts from healthy control subjects but not from patients with asthma that was related to increased expression of activator protein-1 (AP-1) transcription factor in fibroblasts from patients with asthma.…”
Section: Proteoglycan Syntheses Are Closely Regulated By Different Masupporting
confidence: 60%
“…Recent studies show that versican is expressed and accumulates in the lungs of mice in studies of gram-negative lung infection [59, 90], acute lung injury [93], allergen-induced airway inflammation [94], fibrosis [95], cancer [51, 55, 96, 97], and emphysema[98]. Similarly, in humans, versican accumulates in chronic lung diseases such as pulmonary fibrosis [99101], acute respiratory distress syndrome [102, 103], asthma [104, 105], cancer [106], lymphangioleiomyomatosis [107], and chronic obstructive pulmonary disease (COPD) [108, 109]. Whereas numerous studies show that the re-expression and accumulation of versican is a common observation in lung disease, very little is known about the regulation of versican expression or the role of versican in the pathogenesis of lung disease.…”
Section: Versican and Hyaluronan As Components In Lung Diseasementioning
confidence: 99%
“…In addition, increased accumulation of versican has been associated with both small and large airway remodeling seen in autopsy specimens following fatal asthma exacerbations [136]. Subjects with uncontrolled asthma demonstrate increased accumulation of versican in biopsy specimens from their central airways compared to healthy subjects with well controlled asthma [104]. Interestingly, these same subjects also demonstrated a greater number of myofibroblasts per unit area in tissue samples.…”
Section: Chronic Changes To Airway Ecm In Asthmamentioning
confidence: 99%
“…An increasing body of evidence suggests that inflammatory processes in the distal airways contribute to asthma pathogenesis . For example, several studies have shown infiltration of leucocytes and fibroblasts in the alveolar parenchymal tissue . Inflammatory cells implicated in asthma, such as eosinophils, Th2 lymphocytes and mast cells, have also been shown to increase in distal airways compared to healthy controls …”
Section: Introductionmentioning
confidence: 99%
“…Although comprising a subpopulation of all asthmatics, this category has significantly lower quality of life and contributes considerably to the economic burden of asthma. We have previously shown that both central and distal proteoglycans and total collagen levels differ between patients with controlled and uncontrolled asthma, despite equivalent doses of ICS . Considering the proposed role for MCs in remodelling and the broad actions of collagens, the aim of this study was to investigate the composition of specific collagens along with MC phenotypes and their TGF‐β expression in patients with controlled and uncontrolled asthma.…”
Section: Introductionmentioning
confidence: 99%